Pengaruh Organizational Ambidexterity pada Organization Innovation Performance dalam Industri Perbankan Indonesia - Setyawijaya, Balqish; Ekowati, Dian (Universitas Batanghari Jambi, 2024)
In an era of business characterized by rapid technological changes like today, it becomes extremely crucial for organizations to continuously enhance their innovation performance. In the effort to achieve improved innovation performance, companies must implement the concept of organizational ambidexterity to have a positive impact on organizational innovation performance. Therefore, this research focuses on exploring the relationship between exploration strategy and exploitation strategy with organizational innovation performance. Participants in this study are employees working in the banking industry in Indonesia, with a total of 278 respondents. The analysis in this study was conducted using Smart PLS 3.0 software. The research results indicate that both exploration strategy and exploitation strategy have a positive influence on organization innovation performance.